(untitled) (Contemporary Journal of Social Science Review, 2025)
Situated within the evolving discourse of the blue humanities, this research offers a nuanced reinterpretation of Wu Ming-Yi’s The Man with the Compound Eyes, positing the novel as a dynamic meditation on human-ocean entanglements. Through the theoretical lens of Steve Mentz’s Shipwreck Modernity, this research unveils Wu’s narrative as a vision of the ocean not merely as a passive backdrop, but as an agentive and transformative force that reconfigures human subjectivity and ecological awareness, challenging conventional boundaries between human and non-human worlds. The Man with the Compound Eyes navigates the interstitial space between pre-modern ecological harmony and the ruptures of contemporary environmental crises, foregrounding the tensions between traditional ecological knowledge and the incursions of global modernity. The narrative unfolds profoundly human tales of vulnerability, resilience, and displacement amidst the aftermath of ecological devastation. This research posits that Wu’s text orchestrates a paradigm shift, moving away from terrestrial epistemologies to embrace a fluid, oceanic consciousness. In doing so, it subverts anthropocentric paradigms and offers a compelling vision of ecological co-becoming, urging a reimagined ethical engagement with the non-human world. By intricately weaving climate imaginaries, cultural adaptation, and oceanic ontology, The Man with the Compound Eyes transcends conventional narrative forms, emerging as a transformative literary intervention that expands the intellectual frontiers of the Anthropocene and redefines the critical landscape of blue humanities.